Shells that remember: Heavy metals concentrations in Perna Viridis shells from the West coast of peninsular Malaysia - Krishnan, Kumar; Yap, Chee Kong; Badamasi, Muhammad Lawal; Horie, Yoshifumi; Setyawan, Ahmad Dwi (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to study whether shells of the green-lipped mussel Perna viridis can deliver a clear, layer resolved picture of metal bioavailability while also recognising their carbon value. Mussels were purchased by weight without pre order from six south western coast landing sites in Peninsular Malaysia. Shells were measured, the periostracum was scraped and the nacre powdered, and both layers were digested and analysed for copper, iron, nickel, lead and zinc, the periostracum and the nacre showed a consistent hierarchy with iron and lead highest, nickel intermediate, and copper and zinc lower, with site contrasts that were clear and repeatable. These differences indicate real spatial variation in bioavailability that the shell archives over time. We interpret these patterns as an integrated readout that can be repeated with routine landings to build defensible baselines for management. The workflow is rapid and nonlethal and is suitable for long term surveillance. In parallel, the calcium carbonate fraction represents a durable stock that can be retained and beneficially reused on land, linking contamination surveillance with a small carbon contribution to climate action. Overall, the mussel shells procvide a practical tool for mapping hotspots and tracking progress in pollution control. Findings are usable for coastal planning and routine reporting. The present findings are able to answer the heavy metal levels in the P. viridis shell layers of nacrea and periostracum across six sites, compare layer specific and site specific patterns.